Injury Pattern in Fatal Cases of Stab Wound (Medicine Today, 2019)
Introduction: Stabbing is the most common method of homicide as like as other parts of the world. Precise examination of stab wound along with the type of other wounds considering their site, shape, number and orientation of the wounds in relation to each other etc. provide a number of clues which may be of paramount importance in reconstruction and interpretation of the whole events.Materials and Methods: This is a retrospective study carried out in Forensic Medicine Department of Sylhet M.A.G. Osmani Medical College, Sylhet from July 2010 to June 2011 and in the year of July 2017 to June 2018 to observe different patterns of injuries in fatal cases of stab wound. 20 autopsies were included in this study using random sampling.Results: Male(90%) are more victimized than female. The pattern of injury that found to be most common is the penetrating wound of the chest injuring either lung or heart. Second most common injury pattern is the penetrating wound of the chest or abdomen injuring eitherstomach or liver.Another pattern is widely scattered multiple stab wounds both on front and back of the body and the fourth pattern is stab wound of the lower limb causing division of a major blood vessel.Conclusion: The stab wound is deeper than it is long or wide. This means depth is the greatest dimension in case of Stab wound and that is where the danger lies as it is evident in this study.Medicine Today 2019 Vol.31(2): 76-79